Maquiavel e Guicciardini: liberdade cívica e discórdias civis - Marin, Marcelo de Paola (2007)
Based on a comparative study between two publications by Niccolò Machiavelli and Francesco Guicciardini, respectively, the Discorsi sopra la prima deca di Tito Lívio and the Considerazioni intorno ai Discorsi del Machiavelli, we intend to elicit how the main ideas of civil freedom and civil disagreement appear in the political philosophy of each of the authours mentioned. Taking into account examples of ancient Rome, Machiavelli tries to show situations in which civil disagreement enhanced the institutions and guaranteed civil freedom. On the other hand, Guicciardini denies Machiavelli s arguments, facing civil disagreement as an element intrinsically harmful to the maintenance of the political unit. In order to appropriately explain the thoughts of both thinkers, it was necessary to understand the way Guicciardini and Machiavelli conceived the citizens political participation in the governmental institutions. Therefore, studying these Renascentists shows us how the topic civil disagreement is important to reflect the balance and social dynamics of political communities